Case Study of Bilateral Ureteral Stones Complicated by Acute Kidney Injury in a 52-Year-Old Female Patient - Ilmiah, Janiya Abdila; Putri, Imey Pinasty Harianto; Muliana, Atriska Citra; Athalia, Ihza Namira; Shafitri, Shira Shalsabina; Sari, Baiq Merna Merta; Aulia, Rashieka Salma; Prasetya, Rangga Cahya; Indratama, I Nyoman Yudayana; Shiddiq, Muhammad Hilmy As; Josafat, Gantha Narendra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bilateral ureteral stones are a rare clinical manifestation of renal colic, obstructing urine flow, and can cause severe acute kidney injury (AKI) within hours. This case study aims to provide information regarding the diagnosis and management of bilateral ureteral stones causing acute kidney injury in a 52-year-old female patient. This case study uses a descriptive method to describe the current situation, for further analysis and interpretation. Based on anamnesis and physical examination, the patient was diagnosed with Acute Kidney Injury (AKI) stage 3 with a differential diagnosis of Advanced Chronic Kidney Disease (ACKD) stage 4. This condition is caused by urinary tract obstruction due to bilateral ureterolithiasis (stones in both ureters) and proximal right ureteral stenosis, which inhibits urine flow and worsens kidney function acutely and chronically. Complaints of right and left abdominal pain, as well as a history of urinary tract infections (UTIs) and hypertension, support the formation of stones in the urinary tract. The conclusion is that the patient Wirni/P/52 years old/AKI stage 3 dd ACKD stage 4 dt obstructive uropathy + ureterolithiasis infection + normocytic normochromic anemia dt chronic disease + bilateral ureteral stones + right proximal ureteral stenosis.